ANALISIS KINERJA STRUKTUR GEDUNG RUSUN ASN 3 AKIBAT BEBAN GEMPA - Apriliani, Roski; Kudwadi, Budi; Batubara, Ben Novarro (Universitas Pendidikan Indonesia (UPI), 2025)
Rusun ASN 3 Building is a multi-story residential building with height of 54.8 m located in East Kalimantan. For the comfort and safety of the building occupants, an analysis of the effects of earthquake loads is needed. This research analyzed using the response spectrum and time history methods. This research was conducted to determine the maximum drift value and level of structural performance based on ATC – 40. The results obtained were that the maximum drift value due to spectrum response earthquake was 41.6130 mm for X direction and 48.9380 mm for Y direction. The maximum drift value due to time history earthquake, for Chuetsu-oki earthquake it was 33.7160 mm in X direction and 55.3960 mm in Y direction; for Kushirooki earthquake it was 40.9760 mm in X direction and 39.9820 mm in Y direction; for Miyagi_Pre.Off earthquake, it was 53.5150 mm in X direction and 42.9820 mm in Y direction. The level of structural performance of the building due to earthquake loads, was at the Immediate Occupancy (IO) performance level, which means the building was still able to withstand the forces of the earthquake that occurred.Keywords : ATC-40, Spectrum Response, Time History, Dynamic Earthquake, Structural Performance